1999
DOI: 10.1007/s001980050115
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hip Fracture in Men from Southern Europe: The MEDOS Study

Abstract: The aims of this study were to identify risk factors for hip fracture in men aged 50 years or more. We identified 730 men with hip fracture from 14 centers from Portugal, Spain, France, Italy, Greece and Turkey during the course of a prospective study of hip fracture incidence and 1132 age-stratified controls selected from the neighborhood or population registers. The questionnaire examined aspects of work, physical activity past and present, diseases and drugs, height, weight, indices of co-morbidity and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
185
3
19

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(212 citation statements)
references
References 25 publications
5
185
3
19
Order By: Relevance
“…(29) Further, in data provided by Feskanich and colleagues for the Nurses' Health Study, milk accounted for 54% of dairy calcium intake, although this may be lower in some European countries where cheese is a stronger contributor to dairy calcium intake. (30)(31)(32) However, a lower dairy intake from milk in Europe would not have affected the results of this meta-analysis provided that milk intake is a relevant predictor of hip fracture risk overall.…”
Section: Discussionmentioning
confidence: 99%
“…(29) Further, in data provided by Feskanich and colleagues for the Nurses' Health Study, milk accounted for 54% of dairy calcium intake, although this may be lower in some European countries where cheese is a stronger contributor to dairy calcium intake. (30)(31)(32) However, a lower dairy intake from milk in Europe would not have affected the results of this meta-analysis provided that milk intake is a relevant predictor of hip fracture risk overall.…”
Section: Discussionmentioning
confidence: 99%
“…The health benefits associated with tea consumption with respect to the prevention of cancers and cardiovascular disease have been investigated intensively (4); additionally, tea consumption reportedly protects against hip fracture (5,6). Older women who drank tea exhibited higher BMD measurements than did women who did not drink tea (7).…”
Section: Introductionmentioning
confidence: 99%
“…Human studies on dietary flavonoids and bone health have focused on tea because tea has been reported to protect against hip fracture. (11,12) Cellular models and animal studies have found associations between bone health and flavonoids (13)(14)(15) ; therefore, the aim of this study was to examine whether dietary flavonoids (ie, flavonols, flavones, flavanones, catechins, and procyanidins) were associated with markers of bone health in a large cohort of Scottish women. aged 45 to 54 years who first visited our unit between 1990 and 1994.…”
Section: Introductionmentioning
confidence: 99%